Middle Class Rebellion through the Main Characters in Chuck Palahniuk’s Fight Club - Ali Muhammad; Andhika Pratiwi; Ria Herwandar (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2018)
Abstract - This research entitled “Middle Class Rebellion through the Main Characters in Chuck Palahniuk’s Fight Club” analyses the portrayal of the Middle Classes which is depicted through the main characters. These characters are undertaking a Rebellion towards the system of Capitalism that is depicted in the novel Fight Club. The theory used in this research is the theory of the intrinsic element of Characterization by M.H. Abrams and the theory Capitalism by Karl Marx which includes the theory of Alienation and the Struggle of Social Classes. This research focuses on the portrayal of how Middle Classes undertake their Rebellion which is depicted through the main characters in the novel Fight Club by Chuck Palahniuk. This research has found that the two main characters are a depiction of the Middle Class and the Working Class. They rebel against Capitalism by doing small acts of vandalism which escalates into blackmail. The findings are that the real characteristics of modern society of the middle class can be seen  such as consumerism, restless life towards insomnia and workers who identify themselves as not workers.Keywords - Middle Class, Rebellion, Social Class, Marxism, Capitalism